Значення роботи над артикуляцією й дикцією в процесі вдосконалення співочого мовлення - Карпов, В.В. (Культура народов Причерноморья, 2014)
Стаття присвячена актуальним проблемам музичної педагогіки, пов’язаним з опануванням
секретами вокального мовлення, з врахуванням його специфіки в порівнянні з мовленням сценічним, а
тим більше повсякденним. Звертається увага на особливу роль артикуляції й дикції у вдосконаленні
вокальної техніки, у належному розкритті сценічного образу.
Належне опанування артикуляцією й дикцією має безпосередній стосунок до виразності вокального
виконання. Без відповідної артикуляції й дикції немислима підготовка професійного вокаліста Статья посвящена актуальным проблемам музыкальной педагогики, связанным с
постижением секретов вокальной речи, с учетом ее специфики в сравнении с речью сценической, а тем
более обыденной. Обращается внимание на особую роль артикуляции и дикции в усовершенствовании
вокальной техники, в надлежащем раскрытии сценического образа.
Надлежащее овладение артикуляцией и дикцией имеет непосредственное отношение к
выразительности вокального исполнения. Без соответствующей артикуляции и дикции немыслима
подготовка профессионального вокалиста. The article is devoted to the actual problems of the musical pedagogic connected with the
comprehension of the secrets of vocal pronunciation,with paying attention on its peculiarity in comparison with
scene and everyday pronunciation. The author of this investigation takes notice to articulation and elocution as
very important aspect of a sinning technique. A correct possession of articulation and elocution beyond an
importance of other components of singing plays here a special role and therefore it is closely connected with
the expressiveness of the vocal performance. The process of preparation of a professional vocalist is impossible
without an educating of correct diction, without a possessing of a special habit in this meaning.
The author of the article leans upon the works by V.A. Bagadurov, B.O. Bazilikut, L.V. Dmitriyev, U.Y. Yutsevich
and other researches and musical pedagogues. But he previously uses here his own experience as the professor in Crimean University of Culture, Art and Tourism (Simferopol), in Crimean Humanitarian University (Yalta) as
well as the leading actor and singer in Crimean Academic Ukrainian Musical Theatre.